Menentukan Jurusan Perguruan Tinggi untuk Peserta Didik SMK Berdasar Nilai Raport serta Minat dan Bakat dengan Metode Decision Tree Algoritma C4.5 (Studi Kasus SMK Negeri 1 Donorojo Pacitan) - Arif Baktiar; Bambang Soedijono; Alva Hendi Muhammad (LPPM Universitas Merdeka Madiun, 2023)
The purpose of this research is to create a good method to assist in making the right decision in selecting tertiary majors for class XII students at SMK Negeri 1 Donorojo, and also to help agencies, especially SMK Negeri 1 Donorojo and other SMK, to be able to make decisions to determine the potential of each student. The limitation of the problem is to determine college majors for class XII students at SMK Negeri 1 Donorojo based on report cards and interests and talents, and the solution to be produced is a method that can provide an overview of college majors according to students' potential so that they can help agencies schools in guiding students who will continue on to higher education. Methods of data collection using observation and questionnaires (questionnaire), while for data analysis using the stages of Algorithm C4.5. The results showed that accuracy was 45.21%, Class Precision for English was 33.33%, Mathematics was 14.29%, Indonesian was 66.67%, Islamic Religious Education was 36.36%, and Citizenship Education was 0.00%. while for Class Recall English 27.27%, Mathematics 18.18%, Indonesian 70.59%, Islamic Religious Education 30.77%, and Citizenship Education 0.00%. The conclusion from this study is that students' interest in choosing majors in tertiary institutions is not always based on subject scores but more based on other unknown variables or attributes.